How to understand the results of studies of glutamine supplementation. Issue 1 (December 2015) - Wernerman, Jan
Abstract The lack of understanding of the mechanisms behind possible beneficial and possible harmful effects of glutamine supplementation makes the design of interventional studies of glutamine supplementations difficult, perhaps even hazardous. What is the interventional target, and how might it relate to outcomes? Taking one step further and aggregating results from interventional studies into meta-analyses does not diminish the difficulties. Therefore, conducting basic research seems to be a better idea than groping in the dark and exposing patients to potential harm in this darkness.